The linguistic term in Arabic linguistic studies: “Principles of Linguistics” by Khawla Taleb Ibrahimi as a model. - djebbar, kamel (El Omda in Linguistics and Discourse Analysis, 2025)
This article discusses the issue of linguistic terminology in Arabic linguistic studies by tracing this term historically, with the aim of identifying its true sources and epistemological foundations. It is based on the work of the Algerian researcher Khawla Taleb Ibrahimi and her book entitled “Principles of Linguistics.” It seeks to uncover the scientific and cognitive roots of the book in order to provide a general overview of the linguistic schools that influenced Arab linguists in both the Maghreb and the Mashreq. This modest contribution aims at unifying Arabic linguistic terminology, which remains a major challenge in Arabic linguistic studies.